Trimer Enhancement Mutation Effects on HIV-1 Matrix Protein Binding Activities - Alfadhli, Ayna (J Virol, 2016)
The HIV-1 matrix (MA) protein is the amino-terminal domain of the HIV-1 precursor Gag (Pr55Gag) protein. MA binds to membranes and RNAs, helps transport Pr55Gag proteins to virus assembly sites at the plasma membranes of infected cells, and facilitates the incorporation of HIV-1 envelope (Env) proteins into virions by virtue of an interaction with the Env protein cytoplasmic tails (CTs). MA has been shown to crystallize as a trimer and to organize on membranes in hexamer lattices. MA mutations that localize to residues near the ends of trimer spokes have been observed to impair Env protein assembly into virus particles, and several of these are suppressed by the 62QR mutation at the hubs of trimer interfaces. We have examined the binding activities of wild-type (WT) MA and 62QR MA variants and found that the 62QR mutation stabilized MA trimers but did not alter the way MA proteins organized on membranes. Relative to WT MA, the 62QR protein showed small effects on membrane and RNA binding. However, 62QR proteins bound significantly better to Env CTs than their WT counterparts, and CT binding efficiencies correlated with trimerization efficiencies. Our data suggest a model in which multivalent binding of trimeric HIV-1 Env proteins to MA trimers contributes to the process of Env virion incorporation. IMPORTANCE The HIV-1 Env proteins assemble as trimers, and incorporation of the proteins into virus particles requires an interaction of Env CT domains with the MA domains of the viral precursor Gag proteins. Despite this knowledge, little is known about the mechanisms by which MA facilitates the virion incorporation of Env proteins. To help elucidate this process, we examined the binding activities of an MA mutant that stabilizes MA trimers. We found that the mutant proteins organized similarly to WT proteins on membranes, and that mutant and WT proteins revealed only slight differences in their binding to RNAs or lipids. However, the mutant proteins showed better binding to Env CTs than the WT proteins, and CT binding correlated with MA trimerization. Our results suggest that multivalent binding of trimeric HIV-1 Env proteins to MA trimers contributes to the process of Env virion incorporation.